Estudo do perfil de pacientes submetidos a pesquisa de Helicobacter pylori: análise endoscópica e dos fatores determinantes da atividade linfocitária na resposta imunológica gástrica (ROR-Y, FOXP3 e GATA3) - MIRANDA, Ariney Costa de (Universidade Federal do Pará, 2017)
INTRODUCTION: Helicobacter pylori is known for its adaptability to the host may progress to chronic infection using diverse and effective mechanisms of pathogenicity. It has high worldwide incidence and its direct relationship with peptic ulcer, gastritis, gastric carcinoma and lymphoma occurs in a minority of infected individuals. A better understanding of the genetic regulation of gastric immune response, motivated this investigation. OBJECTIVES: Describe the transcription factors of T lymphocytes positive for ROR-γ, FOXP3 and GATA3, correlating them with the intensity, type and degree of activity of gastritis, caused by H. pylori infection METHODS: The study included 50 patients of both sexes who underwent upper gastrointestinal endoscopy with biopsy. Urease test and histology were made for identification and confirmation of infection by the bacteria. Thirty-five samples were sent to the immunopathology laboratory NMT-UFPA to study gene expression of transcription factors of T lymphocytes (ROR- γ, FOXP3 and GATA3) by RT-PCR method. RESULTS: We obtained 48.5% positive H. pylori urease test in patients and 25.7% positive of H. pylori in the histological study. The confirmation of H. pylori held by these two exams was 11.7%. In this sample, 22% of individuals reported having a previous Helicobacter pylori infection. The age and gender of the individuals did not influence the gene expression of the studied factors. The H. pylori positive individuals showed a higher expression of the GATA3 gene with prior infection report, and mild erosive gastritis body classified by the Sydney system via endoscopy. The ROR-γ gene presented with increased expression only when comparing samples with or without positive for H. pylori (histology), by the topography of the inflammatory process evidenced by endoscopy. The terms of the factors in the study were more significant when we used the β-actin gene as standard when compared to the GAPDH gene. CONCLUSIONS: The adult age group analyzed in our sample did not influence the gene expression of the studied transcription factors. 2- There were not found differences in the genes expressions that were studied, related to gender of the sample. 3- There was a significant gene expression not only in the patients that were H. pylori positive (histology), but also in the ones who reported previous infection in our study. 4-To compare the endoscopic findings of the sample using the Sydney system with the gene expression of transcription factors under study, we obtained better agreement only in the degree of activity of gastritis. 5- The transcription factor GATA3 (TH2 response profile) was the highest gene expression in samples with endoscopic gastritis and tested positive for H. pylori. 6- The transcription factor ROR-γ (TH17 response profile) presented with increased expression when comparing samples with the topography of the inflammatory process evidenced by endoscopy, regardless of positive H. pylori (histology). 7- The gene β-actin gene as a constituent standard used in our study was that showed significant results in quantified terms, when compared to the GAPDH gene.